The Influence of Cytochrome P450 Polymorphisms on Pharmacokinetic Profiles and Treatment Outcomes Among Malaria Patients in Sub-Saharan Africa: A Systematic Review - Marwa KJ; Kapesa A; Kamugisha E; Swedberg G (Pharmacogenomics and Personalized Medicine, 2023)
Karol J Marwa,1 Anthony Kapesa,2 Erasmus Kamugisha,3 Göte Swedberg4 1Department of Pharmacology, Catholic University of Health and Allied Sciences, Mwanza, Tanzania; 2Department of Community Medicine, Catholic University of Health and Allied Sciences, Mwanza, Tanzania; 3Department of Biochemistry, Catholic University of Health and Allied Sciences, Mwanza, Tanzania; 4Department of Medical Biochemistry and Microbiology, Uppsala University, Uppsala, SwedenCorrespondence: Karol J Marwa, Department of Pharmacology, Catholic University of Health and Allied Sciences, P.O. Box 1464, Mwanza, Tanzania, Tel +255769861421, Email carol_maro@yahoo.com; karoljuliusmarwa@gmail.comBackground: Sub-Saharan Africa (SSA) population is genetically diverse and heterogenous thus variability in drug response among individuals is predicted to be high. Cytochrome P450 (CYP450) polymorphisms is a major source of variability in drug response. This systematic review presents the influence of CYP450 single nucleotide polymorphisms (SNPs), particularly CYP3A4*1B, CYP2B6*6 and CYP3A5*3 on antimalarial drug plasma concentrations, efficacy and safety in SSA populations.Methods: Searching for relevant studies was done through Google Scholar, Cochrane Central Register of controlled trials (CENTRAL), PubMed, Medline, LILACS, and EMBASE online data bases. The Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines were used. Two independent reviewers extracted data from the studies.Results: Thirteen studies reporting the influence of CYP450 SNPs on plasma concentrations, efficacy and safety were included in the final data synthesis. CYP3A4*1B, CYP3A5*5, CYP2B6*6 and CYP2C8*2 did not affect antimalarial drug plasma concentration significantly. There was no difference in treatment outcomes between malaria patients with variant alleles and those with wild type alleles.Conclusion: This review reports lack of influence of CYP3A4*1B, CYP3A5*3, CYP2C8*3 and CYP2B6*6 SNPs on PK profiles, efficacy and safety in SSA among P. falciparum malaria patients.Keywords: cytochrome P450 polymorphisms, review, antimalarial drugs, sub-Saharan Africa, treatment outcomes and pharmacokinetics